Pattern of Declining Fertility and Associated Factors in Nepal - Acharya, Chandra Mani (The Himalayan Geographers, 2025)
Nepal has experienced a remarkable fertility transition over the past four decades, with the total fertility rate (TFR) declining from 6.3 children per woman in 1976 to the replacement level of 2.1 by 2021. This study explores the trends, patterns, and determinants behind this demographic shift using secondary data from the Nepal Demographic and Health Surveys (NDHS) conducted in 2006, 2011, 2016, and 2022, as well as national census reports and relevant scholarly literature. The analysis reveals that increased contraceptive prevalence, delayed age at marriage, rising levels of female education, and enhanced access to reproductive health services particularly after the legalization of abortion have significantly contributed to reduced fertility. Additionally, socio-economic changes and evolving cultural norms have played crucial roles in shaping reproductive behavior. The study highlights the broader implications of this transition, including a shrinking youth population, a growing working-age demographic, and the potential for Nepal to benefit from a demographic dividend. However, it also emphasizes the urgent need for targeted social and economic policies to ensure that the demographic window is effectively leveraged for sustainable development. This research contributes to the understanding of Nepal’s fertility dynamics and offers policy insights for managing demographic change in similar low-income contexts.